Correlated Functional Oxides Nanocomposites and Heterostructures - Nishikawa, Hiroaki; Iwata, Nobuyuki; Endo, Tamio; Takamura, Yayoi; Lee, Gun-Hwan.; Mele, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces a variety of basic sciences and applications of the nanocomposites and heterostructures of functional oxides. The presence of a high density of interfaces and the differences in their natures are described by the authors. Both nanocomposites and heterostructures are detailed in depth by researchers from each of the research areas in order to compare their similarities and differences. A new interfacial material of heterostructure of strongly correlated electron systems is introduced.
Functional Iron Oxides and Their Heterostructures -- Functional Properties of Polydomain Ferroelectric Oxide Thin Films -- Stress Accommodation and Structural Distortions at Correlated Oxide Interface -- The Influence of Different Additives on MgB2 Superconductor Obtained by ex-situ Spark Plasma Sintering: Pinning Force Aspects -- Infrared Spectra in Oxide Nanocomposites/Minerals -- Self-Assembled Nanocomposite Oxide Films -- Functionality in Insulating Oxide Thin Films: Work Function Control and Polar Surface -- Material Design of Metal Oxide Nanowires and Their Promises -- Atomic Processes of Pulsed Laser Deposition During Growth of Alkaline Earth Oxide Thin Films.
Keywords: Surfaces (Technology).; Thin films; Microtechnology; Microelectromechanical systems; Crystallography; Optical materials; Surfaces, Interfaces and Thin Film; Microsystems and MEMS; Crystallography and Scattering Methods; Optical Materials